Sustainable Community Development for Developing of Coastal Areas in Alor Regency, East Nusa Tenggara, Indonesia - Saparita, Rachmini; Nanang Surachman, Diki; M. Astro, Hendarwin; Sukirno, Sukirno; Karsani Apriliyadi, Eki (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2020)
Community empowerment activities are carried out in Alor Regency - East Nusa Tenggara through the application of fish-based food processing technology in 2018 & 2019, aimed at improving the community’s economy in the coastal area of Alor Island and building the concept of sustainable empowerment. The intervention stage is approached by the Community Capacity Building method. Community empowerment carried out through the transfer of knowledge and technology with continuous assistance has implications for improving coastal communities’ skills and the use of technology to increase added value to get better income. In order for community empowerment to be sustainable, LIPI and the local government of Alor Regency have developed a community empowerment concept that local governments can implement to develop their areas and communities in a better and more competitive direction. By collaborating between R & D institutions, local governments, and business actors (triple helix) and the market, it is hoped that the economy of the people in the coastal area of Alor Island will run well and can be a lever in the development of areas based on the use of technology in the community.